PELAKSANAAN E-GOVERNMENT PADA SISTEM APLIKASI KEPEGAWAIAN TERINTEGRASI (SAKTI) DI KABUPATEN ROKAN HULU TAHUN 2019-2020 - Elsa Prisanda; Auradian Marta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The Integrated Personnel Application System or Sakti is an E-Government program specifically designed to make it easier to handle personnel data management and is also designed to be able to manage services at the Education and Training Personnel Board (BKPP) of Rokan Hulu Regency in providing information to all State Civil Apparatuses ( ASN) Rokan Hulu Regency. The problem in this research is that the implementation of the Integrated Personnel Application System (Sakti) in Rokan Hulu Regency has not been optimal due to several determining factors that underlie the readiness to implement E-Government. The purpose of this study was to determine the implementation of E-Government in the Integrated Personnel Application System (Sakti) in Rokan Hulu Regency in 2019-2020.This study uses Indrajit's theory, which is related to the determinants of readiness for the implementation of E-Government in the regions. The research approach used is a qualitative approach. This type of research is descriptive. The research location is in Rokan Hulu Regency, precisely in the Education and Training Personnel Agency of Rokan Hulu Regency. The types and sources of research data are divided into primary data with purposive informant retrieval techniques and secondary data in the form of supporting data related to Sakti.The results of this study are that the Integrated Personnel Application System (Sakti) by the Rokan Hulu Regency Government in 2019-2020 is not optimal, this is because the level of readiness of E-Government has not met the indicators. The problems that underlie the process of implementing this system are related to the implementation process that has not been evaluated, so that there are several obstacles that hinder it, the telecommunications infrastructure that has not been fulfilled, the absence of regional regulations/regents and agency/agency regulations, the absence of a special budget for the Application System program. Integrated Personnel (Sakti), access to the Integrated Personnel System portal which is often down, makes many State Civil Apparatus not aware of this application and still performs personnel administration manually, as well as the role of regional heads of agencies who are not yet serious in supporting the implementation of E-Government. because they are busy with their own internal affairs. Keywords: E-Government, Integrated Personnel Application System (Sakti), Indicator